Bioakumulasi kobalt dan nikel pada tanaman kalakai (Stenochlaena palustris (burm. F.) Bedd) di tanah gambut bekas terbakar desa Pakning Asal, Bengkalis - Oktavia Surya Indra; Tengku Nurhidayah; Sofia Anita (Jurnal Zona, 2019)
The last 5 years, palm oil plantation in Pakning Asal, Bengkalis were burned in different frequencies. There were unburned soil and burned soil in several times (2-3 times). Land fires affect the physical chemistry of the soil including macro and micro nutrients in soil as well as surrounding plant growth. One of them is kalakai usually made by vegetables in community. The purpose of this study were to analyze the composition of Co and Ni on roots, stems and leaves of kalakai on peat soil unburned soil and burned soil in several times and determine the content of Co and Ni metal in suitable and safe plants for consumption by the community based on the Acceptable Daily Intake (ADI). Co and Ni analysis was carried out using the Atomic Absorption Spectrophotometer (AAS).The results of the analysis Co content in plants increases on peat unburned soil and Ni content increases on burned peat soil. Based on Acceptable Daily Intake (ADI) on kalakai that grow on unburned peat soil and burned several times 81,76 µg/kg BB/hari dan 57,97 µg/kg BB/hari for Co and 112,56 µg/kg BB/hari dan 119,763 µg/kg BB/hari for Ni. Based on ANOVA test performed with p kurang dari 0.05 can be concluded that there is a significant difference in roots, stems and leaves growing on peat soil unburned and burned several times.